Studying Cytotoxic T-lymphocyte- Associated Antigen-4 (CTLA-4) gene Polymorphism in a Sample of Iraqi Women with Polycystic Ovarian Syndrome - Haneen Subhee Shaheed; Wassan Abdul-Kareem Abbass; Suzan Yousif Jasim (College of Pharmacy / Mustansiriyah University, 2019)
Polycystic ovarian syndrome (PCOS) considers as the most common disorder among women during reproductive age. Its common features involve hyperandrogenism, chronic anovulation, and weight gain. Till now, the pathogenesis of PCOS stay unknown, and   there is evidence considered PCOS as a low-grade inflammatory disease. Polycystic ovarian syndrome is associated with a variety of endocrine and metabolic disturbances. The present study was designed to detect the role of (CTLA-4) gene polymorphism (rs733618) with PCOS. A total of 60 PCOS patients and 30 healthy women, matching in average age and body mass index (BMI), were enrolled in this study. Patients with PCOS were attend to AL - Nahrain University High Institute for Infertility Assisted Reproductive Technology, in Baghdad between Septembers to December/2018. Blood samples were aspirated from both groups to detection (CTLA-4) gene polymorphism (rs733618) by tetra-primer amplification-refractory mutation system based on real time polymerase chain reaction (ARMS-qPCR). The obtained results revealed normal genotyping for both groups. The result of current study confirms that there is no role of (CTLA-4) gene polymorphism (rs 733618) in PCOS.